1985
DOI: 10.1007/bf00282237
|View full text |Cite
|
Sign up to set email alerts
|

Sera from Type 2 (non-insulin-dependent) diabetic and healthy subjects contain different amounts of a very low molecular weight growth peptide for vascular cells

Abstract: Summary. Diabetic angiopathy may be due, in part, to increased growth in vascular cells. We have investigated serum growth factors in Type 2 (non-insulin-dependent) diabetic and healthy subjects and their effect on cultured human arterial smooth muscle cells and fibroblasts. Removal of the dialyzable serum fraction (mol. wt. < 12,000) reduced the growth effect of the diabetic sera by 37% (2p < 0.005) and of the nondiabetic sera by only 8% (2p < 0.01). In contrast, there was no difference in growth stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…An as yet unidentified growth peptide of very low molecular weight appears to be responsible. 4 Umeda et al, 22 however, reported that plasma from patients with insulin-dependent diabetes was less capable of stimulating DNA synthesis in cultured smooth muscle cells from rat aorta than was plasma from control subjects. We found that the cellular growth kinetics of injured aortic intima-media did not differ in healthy and in streptozocindiabetic rats.…”
Section: Influence Of Diabetesmentioning
confidence: 94%
“…An as yet unidentified growth peptide of very low molecular weight appears to be responsible. 4 Umeda et al, 22 however, reported that plasma from patients with insulin-dependent diabetes was less capable of stimulating DNA synthesis in cultured smooth muscle cells from rat aorta than was plasma from control subjects. We found that the cellular growth kinetics of injured aortic intima-media did not differ in healthy and in streptozocindiabetic rats.…”
Section: Influence Of Diabetesmentioning
confidence: 94%